2011
DOI: 10.1039/c1ob06195j
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis and cytotoxic activity of isomeric phytosphingosine derivatives

Abstract: New phytosphingosine analogues have been conceived, synthesised and their cytotoxicity in B16 murine melanoma cells tested. These compounds embed an isomeric substitution pattern resulting from a formal permutation of the C-2 and C-4 substituents along the aliphatic skeleton of the original sphingoid base. Five different stereoisomers have been accessed through regio- and stereocontrolled opening of the oxirane of long chain epoxyamine precursors. The corresponding N-hexyl and N-octanoyl derivatives have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…For example, in murine cell lines, sphingosine, dihydrosphingosine, and C6-ceramide are cytotoxic for murine P388 leukemia cells (EC 50 , 2.5 to 5.0 μM) and murine multi-drug resistant P388 leukemia cells (EC 50 , 5.0 to 10.0 μM) (Klostergaard et al, 1998). Phytosphingosine and phytosphingosine derivatives are cytotoxic to murine melanoma B16 cells (10.0 to 50.0 μM; IC 50 , 15 μM) (Rives et al, 2011). In human cells and cell lines, sphingosine is cytotoxic for DLD-1 cells (LD 50 , 26.7 μM) (Sugawara et al, 2006), WiDr cells (LD 50 , 22.9 μM) (Sugawara et al, 2006), Caco-2 colon cancer cells (LD 50 , 24.2 uM) (Sugawara et al, 2006) and HL-60 human promyelocytic leukemia cells (10 μM) (Johnson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in murine cell lines, sphingosine, dihydrosphingosine, and C6-ceramide are cytotoxic for murine P388 leukemia cells (EC 50 , 2.5 to 5.0 μM) and murine multi-drug resistant P388 leukemia cells (EC 50 , 5.0 to 10.0 μM) (Klostergaard et al, 1998). Phytosphingosine and phytosphingosine derivatives are cytotoxic to murine melanoma B16 cells (10.0 to 50.0 μM; IC 50 , 15 μM) (Rives et al, 2011). In human cells and cell lines, sphingosine is cytotoxic for DLD-1 cells (LD 50 , 26.7 μM) (Sugawara et al, 2006), WiDr cells (LD 50 , 22.9 μM) (Sugawara et al, 2006), Caco-2 colon cancer cells (LD 50 , 24.2 uM) (Sugawara et al, 2006) and HL-60 human promyelocytic leukemia cells (10 μM) (Johnson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Within physiologic concentrations (4.0 -13.2 µg/ml for total fatty acids and 0.5 -5.0 µg/ml for sphingoid bases (Brasser et al 2011a, Brasser et al 2011b), salivary lipids exhibit potent antimicrobial activity against a variety of oral bacteria without apparent harm to eukaryotic cells of the oral mucosa. However our lab recently showed that while sphingoid bases are nontoxic to DCs at low concentrations they are extremely toxic to These results are similar to other studies showing dose-dependent cytotoxicity of sphingosine and other sphingoid base derivatives against immortalized human endothelial cells (HUVECtert cells) (Rozema et al 2012), human epidermoid carcinoma KB cells (Shirahama et al 1997), murine P388 myeloid leukemia cells (Klostergaard et al 1998), and murine B16 melanoma cells (Rives et al 2011). However, little is known about the effects of sphingoid bases on normal (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…With the discovery of sphingoid base antimicrobial activity towards P. gingivalis, it is important to establish the cytoxocity of sphingoid bases against host cells, particularly in the range of antimicrobial activity against P. gingivalis that falls within normal physiologic concentrations (e.g. 5-20 µM; (Brasser et al 2011a, Brasser et al 2011b cytotoxic for other eukaryotic cell types as well and several sphingoid base derivatives have been selected for their cytotoxic properties and studied as potential treatments for cancer cells (Klostergaard et al 1998, Rives et al 2011, Rozema et al 2012, Shirahama et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest a therapeutic potential of using sphingolipid cytotoxicity in anti-cancer therapies. Phytosphingosine derivatives have been shown to be cytotoxic to murine melanoma B16 cells at concentrations > 10-50 M. Natural phytosphingosine had an IC 50 at 15 M in murine melanoma B16 cells (Rives et al 2011). D-sphingosine, dihydrosphingosine and C 6ceramide were shown to have an ED 50 of 2.5-5 M on murine P388 leukemia cells (Klostergaard et al 1998).…”
Section: 3mentioning
confidence: 99%